Quality Management in Islamic Education: Philosophical, Juridical and Sociological Foundations - Jaini Mukhlis; Nur Afif (SUJANA: Education and Learning Review, 2025)
Quality management in Islamic educational institutions has attracted growing scholarly attention, yet existing studies tend to examine its philosophical, juridical and sociological dimensions in isolation rather than as a coherent system. This paper examines the policy foundations of school-based quality management in Islamic education in Indonesia and proposes an integrated three-pillar framework that addresses this gap. Using a systematic literature review methodology guided by the PRISMA 2020 framework, the study synthesises theoretical and empirical sources drawn from Scopus-indexed and peer-reviewed publications alongside primary Indonesian regulatory instruments. The analysis confirms that sustainable quality improvement in Islamic schools depends on the coherent alignment of three interdependent foundations: a philosophical foundation rooted in Islamic normative values including ihsan, amanah, ta'awun and tawazun; a juridical foundation grounded in the hierarchy of national education regulations from the 1945 Constitution through the National Education System Law to the 2019 Pesantren Law; and a sociological foundation that keeps institutional practice responsive to the evolving quality expectations of Muslim communities. Each pillar is shown to depend on the others for its effective functioning, with the philosophical pillar animating regulatory compliance, the juridical pillar giving normative commitments enforceable expression, and the sociological pillar ensuring that both remain accountable to genuine community needs. Principal leadership, integrative curriculum design and the PDCA quality assurance cycle are identified as the primary mechanisms through which the three foundations are operationalised in practice. The findings extend and integrate earlier research on Islamic educational leadership, school-based management and institutional quality governance in the Indonesian context.